Growth and Development of Black-Boned Chicken Embryonic Stem Cells for Culture Meat using Different Serums as Medium - P. Promtan; J. Panatuk; W. Kongbuntad; D. Amornlerdpison; Y. Nanta; N. Pripwai; W. Thaworn; W. Pattanawong (Tropical Animal Science Journal, 2023)
This research was conducted to investigate the growth performance of black-boned chicken embryonic stem (ES) cells for the future development of cultured meat. Black-boned chicken ES cells were isolated and cultured from fertilized eggs. The treatments applied were: fetal bovine serum (FBS) (T1), commercial chicken serum (SCK) (T2), Pradu Hang Dam chicken serum (PDC) (T3), and black-boned chicken serum (BBC) (T4). Black-boned chicken ES cells were cultured at 37.0 Â°C in a humidified environment of 5% CO2, for 10 days. The growth of black-boned chicken ES cells concentration was measured by the absorbance at 450 nm. A haemocytometer was used to count the number of black-boned chicken ES cells. Comparing the protein content of cultured meat and chicken meat was collected for combustion and proximate analysis. All collected data were analyzed using ANOVA in a completely randomized design. T4 tended to have a higher number and growth rate than the other groups, followed by T3, T2, and T1, respectively. When counted ES cells final, T4 had a significantly higher number and growth rate than the other groups (p<0.001). Comparing the protein content, it was found that cultured meat had significantly more protein than the other groups (p<0.001), and characteristics (alignment and cross-section of muscle fibers) were not different from chicken cells. Finally, the cultivation of black-boned chicken ES cells necessitates the use of a medium containing black-boned chicken serum in the growth and development of black-boned Chicken ES cells for culture meat.